Nuevos registros de especies y un hospedero vegetal del género Heilipus Germar (Curculionidae: Molytinae: Hylobiini) para Colombia - Díaz , Valentina; Equihua-Martínez , Armando; Romero-Nápoles, Jesús; Valdez-Carrasco, Jorge; Vallejo-Espinosa, Luis Fernando (Instituto de Ecología, A.C., 2021)
Heilipus Germar, 1824 is a genus of curculionids with distribution in the American continent. It is currently made up of 88 species, some of which are considered pests in crops with high commercial value, such as avocado (Persea americana Mill.) and soursop (Annona muricata L.). Despite its importance, the genus has not been studied enough and only the habits and host plants of 12 species are known. In Colombia, information on this group is also scarce and the most recent list dates from 1986, which reports 15 species. With the objective of updating the knowledge about the Heilipus species present in Colombia, ten museums and entomological collections in the country were visited in search of specimens of this genus. During the visit to the collections, were found specimens of H. discoides (Fabricius), H. draco (Fabricius), H. empiricus (Pascoe), H. guttiger (Champion), H. longirostris (Champion), H. osculatii Guérin and H. tetanicus (Pascoe), which constitute new records for the country. With these results, the number of Heilipus species present in Colombia increases to 23, an amount that positions the country as the second with highest diversity of the group after Brazil. It is noteworthy the finding of the host plant and identification of the habit of H. longirostris, a species that in its larval stage borers seeds of Aniba sp. Probably the number of Heilipus species present in Colombia is higher; however, the absence of an identification key and the lack of a formal review of the group make it difficult determination species, both those already described and those that may be new to science.